"Nothing in Life but Death": Aleksandr Zel'dovich's Target in Conversation with Lev Tolstoy's Philosophy of the Value of Death. Issue 3 (July 2014) - DeBlasio, Alyssa
<x xml:space="preserve">Abstract</x> In this article I investigate the extent to which we may view Aleksandr Zel'dovichs' film Target (Mishen', 2011)—a futuristic adaptation of Anna Karenina—as a cinematic interlocutor for Tolstoy's philosophical position on death. In particular, I unpack Tolstoy's formula for the value of the meaning of death, which he expressed in a mathematical equation in prose that he based on Newton's Law of Universal Gravitation. I put Tolstoy's position on death in conversation with the fictional world of Target, where the protagonists chase immortality by seeking out a source of eternal youth deep in the Altai Mountains. Through an analysis of Tolstoy's philosophical and fiction works, as well as Zel'dovich's own statements on the connection of his film to Tolstoy's canon, I will show the central role of Tolstoy's Newtonaian formula in linking his theoretical works to his fiction masterpieces, and the way that the youth‐hungry society portrayed in Target is in the philosophically interesting position of representing the very opponent to which Tolstoy's Newtonian formula was directed.